THE EFFECT OF INTELLECTUAL QUOTIENT, LEARNING BEHAVIOR, AND STUDENTS’ PERCEPTION ABOUT LECTURER’S COMPETENCE ON IFRS UNDERSTANDING LEVEL OF ACCOUNTING STUDENTS IN PUBLIC UNIVERSITIES IN MAKASSAR - Suhartono, .; Fatimah, St; Burhanuddin, . (PEOPLE: International Journal of Social Sciences, 2018)
This research aims to find out the influence of intellectual quotient, learning behavior, and the students’ perception about the competence of the teacher on the level of International Financial Reporting Standards understanding. The population was the accounting students of State Islamic University of Alauddin Makassar, Hasanuddin University, and State University of Makassar which was taken by using random sampling method, and resulted 75 respondents. Compound regression was utilized as the hypothesis test. The result reveals that intellectual quotient and learning behavior partially influence significantly positive on the level of International Financial Reporting Standards understanding, while the students’ perception about the competence of the lecturer does not influence partially. Therefore, intellectual quotient, learning behavior and the students’ perception about the lecturer competence simultaneously have an effect on the level of International Financial Reporting Standards understanding.